Expanding CXCR4 variant landscape in WHIM syndrome: integrating clinical and functional data for variant interpretation - Zmajkovicova, Katarina; Nykamp, Keith; Blair, Grace; Yilmaz, Melis; Walter, Jolan E. (Frontiers in Immunology, 2024)
Warts, Hypogammaglobulinemia, Infections, Myelokathexis (WHIM) syndrome is a rare, combined immunodeficiency disease predominantly caused by gain-of-function variants in the CXCR4 gene that typically results in truncation of the carboxyl terminus of C-X-C chemokine receptor type 4 (CXCR4) leading to impaired leukocyte egress from bone marrow to peripheral blood. Diagnosis of WHIM syndrome continues to be challenging and is often made through clinical observations and/or genetic testing. Detection of a pathogenic CXCR4 variant in an affected individual supports the diagnosis of WHIM syndrome but relies on an appropriate annotation of disease-causing variants. Understanding the genotypic-phenotypic associations in WHIM syndrome has the potential to improve time to diagnosis and guide appropriate clinical management, resulting in a true example of precision medicine. This article provides an overview of the spectrum of CXCR4 variants in WHIM syndrome and summarizes the various lines of clinical and functional evidence that can support interpretation of newly identified variants.